2021
DOI: 10.31124/advance.17082719.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-Saharan Africa's Biomedical Journal Coverage in Scholarly Databases: A comparison of Web of Science, Scopus, EMBASE, PubMed, African Index Medicus and AfricanJournals Online

Abstract: <p>Data is freely available online doi: 10.17632/52pncd8zmy.1</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…At the African‐regional level, Asubiaro (2022a) is the only article that compared the journals from Africa in two or more research indexing databases. Asubiaro (2022a) focused on Sub‐Saharan African countries' journals in Web of Science and Scopus, though with a focus on biomedical journals. Asubiaro (2022a) found that less than 10% of journals from Sub‐Saharan Africa were indexed in the Web of Science and Scopus.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…At the African‐regional level, Asubiaro (2022a) is the only article that compared the journals from Africa in two or more research indexing databases. Asubiaro (2022a) focused on Sub‐Saharan African countries' journals in Web of Science and Scopus, though with a focus on biomedical journals. Asubiaro (2022a) found that less than 10% of journals from Sub‐Saharan Africa were indexed in the Web of Science and Scopus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Asubiaro (2022a) focused on Sub‐Saharan African countries' journals in Web of Science and Scopus, though with a focus on biomedical journals. Asubiaro (2022a) found that less than 10% of journals from Sub‐Saharan Africa were indexed in the Web of Science and Scopus. Other relevant studies were outdated and only included an ordinary count of journals in the Journal Citation Report (JCR) of the Web of Science without comparison to other research indexing databases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies in gray literature that were not peer reviewed would have not have been eligible for inclusion in this review. Despite using rigorousAU : Pleasenotethatthespellingofthewor search strategies without language restrictions, studies published in journals not indexed in MEDLINE and EMBASE were not captured [259][260][261][262][263]. Given the focus on this review and the heterogeneity in aims and methodologies of included studies, risk of bias assessment to understand how effect size may have been compromised by bias is not applicable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%